Penggunaan Monroe’s Motivated Sequence untuk Meningkatkan Keterampilan Publik Speaking Mahasiswa dalam Menyampaikan Pidato Persuasif - Erna Irawati (Universitas Mathla'ul Anwar Banten, 2017)
This research aims to know the teaching learning process of speaking IV class by using Monroe’s motivated sequence on persuasive speech topic and to improve students’ public speaking skill in delivering persuasive speech by using Monroe’s motivated sequence as a method of organizing persuasive speech. The research method used in this research is class action research with two cycles which conducts two actions per cycle. Data is got by performance test, observation, giving questionnaire and interview. The result of this research shows that teaching learning process of speaking IV class by using Monroe’s motivated sequence on persuasive speech topic has increased the students’ activeness and involvement in every cycle. The average of students’ activity in first cycle is 70.00% and got increased to 81.66% in second cycle. Students’ public speaking skill in delivering persuasive speech increased significantly proved by average of performance test result which increase from 71,70 in cycle 1 to 78,00 in cycle 2 with 75% class achievement. The interview results shows that students are interested in learning persuasive speech by using Monroe’s motivated sequence because it eases them to organize and deliver persuasive speech.